The predictive value of immune inflammation indexes for the risk of fracture in patients with osteoporosis: a systematic review and meta-analysis - Xu, Yawei; He, Xiaoming; Zhang, Xu; Meng, Shilong; Wang, Chengjie; Yuan, Yifeng; Shi, Xiaolin; Liu, Kang (Frontiers in Endocrinology, 2025)
BackgroundThis study aims to elucidate the value of immune inflammation indexes like neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), as well as systemic inflammation response index (SIRI) in fracture risk prediction among the osteoporosis population and the extent of their association.MethodsPubMed, Embase, Web of Science, the Cochrane Library, CNKI, as well as Wanfang were thoroughly retrieved until March 22, 2025. The primary outcome measure was the link of the immune inflammation indexes to fracture risk in osteoporotic people. The consistency of findings and possible origins of heterogeneity were examined via sensitivity and subgroup analyses. Data analysis was enabled by STATA 18.0 and Review Manager 5.4.ResultsThis meta-analysis encompassed eight trials on 3,769 participants. The summary findings indicated that in studies considering categorical variables, NLR (odds ratio (OR) =1.73, 95% confidence interval (CI): 1.40-2.14; p<0.00001), LMR (OR = 0.85, 95% CI: 0.77-0.93; p=0.0007), as well as SII (OR = 1.01, 95% CI: 1.00-1.01; p=0.008) had a significant link to fracture risk in the osteoporosis group, while no such correlation was seen for PLR (p=0.10) and SIRI (p=0.32). In continuous variable analyses, all indexes exhibited a significant connection with the likelihood of fracture. The subgroup analysis indicated that the classification of osteoporosis may affect the prognostic performance of immune inflammation indexes.ConclusionThe immune inflammation index NLR, LMR, and SII possess substantial predictive value for fracture risk in osteoporotic individuals. Moreover, the association between SIRI and fracture risk should be interpreted with caution, as it is derived from only two studies. Nevertheless, several limitations must be acknowledged: most included studies adopted retrospective designs, the study populations were predominantly Asian, and issues such as potential publication bias and result instability cannot be excluded. Therefore, further high-quality investigations are warranted to substantiate our findings.Systematic review registrationPROSPERO, identifier CRD420251053366.